2015
DOI: 10.1111/ppe.12172
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Thyroid Dysfunction during Gestation, Preterm Delivery, and Birthweight. The Infancia y Medio Ambiente Cohort, Spain

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
71
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 33 publications
9
71
1
Order By: Relevance
“…These findings are in agreement with a previous study showing associations between low FT4 concentrations (<2.5 th percentile) at median 13 weeks of pregnancy and an increased risk of preterm delivery [19]. However, null associations have been reported by other studies for low FT4 in early pregnancy [4245] and for continuous measures of FT4 sampled in the first half of gestation [46, 47]. Currently, there are no published data on the relationship of total T3 concentrations with PTB.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with a previous study showing associations between low FT4 concentrations (<2.5 th percentile) at median 13 weeks of pregnancy and an increased risk of preterm delivery [19]. However, null associations have been reported by other studies for low FT4 in early pregnancy [4245] and for continuous measures of FT4 sampled in the first half of gestation [46, 47]. Currently, there are no published data on the relationship of total T3 concentrations with PTB.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, this finding suggests that the third trimester of pregnancy, when the fetus significantly increases in size, is an important window of susceptibility to PM 2.5 exposure. Shields et al (2011), Medici et al (2013), and León et al (2015), as well as our study, report an inverse association between maternal FT 4 and birth weight, which is opposite to cord blood FT 4 . In a study of pregnant women without history of thyroid dysfunction, it has been shown that lower concentrations of FT 4 in maternal blood were related with increased placental growth (Bassols et al 2011).…”
Section: Discussionsupporting
confidence: 65%
“…Previous epidemiological studies have investigated potential IMH‐associated alterations in birthweight . A recent large cohort study from Rotterdam indicated that among euthyroid women, a high FT4 level but not TSH level, is related to SGA .…”
Section: Discussionmentioning
confidence: 99%
“…For example, van Mil et al found that maternal hypothyroxinaemia is associated with larger fetal and infant head sizes. Evidence from León et al also showed that IMH results in higher birthweight. In contrast, Su et al found that isolated hypothyroxinaemia is related to SGA, whereas other studies found no associations between IMH and low birthweight or SGA …”
Section: Introductionmentioning
confidence: 89%